Ictal perfusion changes associated with seizure progression in the amygdala kindling model in the rhesus monkey. (15th July 2015) - Cleeren, Evy; Casteels, Cindy; Goffin, Karolien; Janssen, Peter; Van Paesschen, Wim
Summary Objective Amygdala kindling is a widely used animal model for studying mesial temporal lobe epileptogenesis. In the macaque monkey, electrical amygdala kindling develops slowly and provides an opportunity for investigating ictal perfusion changes during epileptogenesis. Methods Two rhesus monkeys were electrically kindled through chronically implanted electrodes in the right amygdala over a period of 16 and 17 months. Ictal perfusion single photon emission computed tomography (SPECT) imaging was performed during each of the four predefined clinical stages. Results Afterdischarge duration increased slowly over 477 days for monkey K and 515 days for monkey S (18 ± 8 s in stage I; 52 ± 13 s in stage IV). During this time, the animals progressed through four clinical stages ranging from interrupting ongoing behavior to bilateral convulsions. Ictal SPECT perfusion imaging showed well‐localized but widely distributed regions of hyperperfusion and hypoperfusion, in both cortical and subcortical structures, at every seizure stage. A large portion of the ictal network was involved in the early stages of epileptogenesis and subsequently expanded over time as seizure severity evolved. Significance Our data indicate that the different mesial temporal lobe seizure types occur within a common network affecting several parts of the brain, and that seizure severity may be determined by seizure‐induced epileptogenesis within a bihemispheric network that is implicated from the start of the process.